Molten salt phase change energy storage material as well as preparation method and application thereof
The preparation of molten salt phase change energy storage materials through vacuum impregnation of graphene aerogel and solar salt, which solves the problems of low thermal conductivity and easy leakage, significantly improves the thermal conductivity and phase change stability, and is suitable for high-temperature thermal energy storage and manage.
Patent Information
- Application Number
- CN202411301047.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-18
- Publication Date
- 2024-12-31
- Estimated Expiration
- 2044-09-18
AI Technical Summary
Existing molten salt phase change materials have problems of low thermal conductivity and easy leakage, which limits their application efficiency in high-temperature thermal energy storage and management.
The phase-change energy storage material of molten salt is prepared by vacuum impregnation method of graphene aerogel and solar salt, so that molten salt can penetrate the pores of graphene aerogel evenly, combining the high porosity of graphene and the phase-change energy storage of molten salt. Characteristics, significantly improve thermal conductivity and phase transition stability, and prevent molten salt from leaking.
It significantly improves thermal conductivity and phase transition stability, ensures that molten salt is not easily leaked, and is suitable for energy storage of electronic equipment, photothermal conversion devices and systems with strict requirements, and is especially suitable for photothermal storage in solar thermal power plants.
Smart Images

Figure CN119220228A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of molten salt phase change materials, and in particular to a molten salt phase change energy storage material and a preparation method and application thereof. Background Art
[0002] In heavy industries such as steel, cement, and glass manufacturing, the large amount of heat energy generated by high-temperature processes is often not fully utilized, resulting in huge energy waste. The recovery and reuse of the large amount of waste heat generated by industry has gradually become a key strategy for energy conservation, emission reduction, and energy efficiency improvement.
[0003] In recent years, with the rapid development of energy storage technology, molten salt phase change energy storage materials have received widespread attention due to their application potential in the field of medium and high temperature thermal energy storage. Molten salt phase change energy storage materials provide an effective thermal energy storage and management solution for the above industries due to their ability to work stably in high temperature environments. Molten salt phase change energy storage materials can absorb high-temperature waste heat during industrial production processes and release this heat in a controlled manner when needed, which can be used in production processes or converted into electrical energy. This can not only improve energy efficiency, but also help reduce carbon emissions from industrial production and support sustainable development goals. In addition to traditional industries, molten salt phase change energy storage technology has gradually been applied to fields such as power generation, solar power generation, and waste heat recovery systems, showing broad market potential.
[0004] Zhang and other researchers used porous ceramics and molten salts to prepare a new type of composite phase change material. Molten salt is mainly composed of 60% sodium nitrate (NaNO3) and 40% potassium nitrate (KNO3). This mixture is called "solar salt". Solar salt is widely used in medium and high temperature thermal energy storage materials due to its appropriate melting point, large energy storage density, low cost and excellent thermal stability. This material not only improves the thermal conductivity and heat transfer properties of molten salt by infiltrating solar salt into porous silicon carbide (SiC) ceramics, but also enhances the heat storage density through the open cell structure with high porosity. However, the porous carbide is not airtight, and the material still has problems such as low thermal conductivity and easy leakage. Xiao and other researchers developed a new type of molten salt / metal foam / graphene nanoparticle phase change composite material. The molten salt used by the research team is mainly HITEC salt and solar salt. Among them, the composition of HITEC salt is 40% sodium nitrate (NaNO2), 7% potassium nitrate (KNO3) and 53% potassium nitrate (KNO3). This material combines the high latent heat properties of molten salt and the excellent thermal conductivity of graphene, but it still has problems such as low thermal conductivity and easy leakage. Summary of the invention
[0005] The present application provides a molten salt phase change energy storage material and a preparation method and application thereof, aiming to solve the technical problems of low thermal conductivity and easy leakage of existing molten salt phase change materials.
[0006] In order to achieve the above objectives, the present application adopts the following technical solutions.
[0007] In a first aspect of the present application, a method for preparing a molten salt phase change energy storage material is provided, comprising:
[0008] S1, mixing NaNO3 and KNO3 in a mass ratio of 6:4, grinding and heating to 400°C to melt, cooling and grinding again to obtain a eutectic salt;
[0009] S2, dispersing the few-layer graphene oxide and sodium ascorbate in water, and mixing them evenly to obtain a slurry; the slurry is subjected to hydrothermal treatment and then freeze-dried to obtain a graphene aerogel;
[0010] S3, dissolving the eutectic salt in water to prepare a saturated solution, and immersing the graphene aerogel in the saturated solution under vacuum;
[0011] S4, freeze-drying the impregnated product to obtain a molten salt phase change energy storage material.
[0012] In some embodiments, the few-layer graphene oxide is prepared by the following method:
[0013] Mix graphite and sulfuric acid evenly, add sodium nitrate and phosphorus pentoxide, stir at 80-100°C for 12-24h, separate and collect the solid phase, wash and shade-dry to obtain the precursor;
[0014] The precursor is dispersed in excess concentrated sulfuric acid, and potassium permanganate is slowly added thereto, stirred at -10 to 0°C, and then diluted with water, and then heated to 90°C, and hydrogen peroxide is added until the solution turns bright yellow to obtain a dispersion;
[0015] The dispersion is diluted with water, centrifuged at a speed of 5000-7000 r / min to remove multilayer graphene oxide, and then centrifuged at a speed of 10000-12000 r / min to remove impurities, and the concentrated solution obtained by centrifugation is freeze-dried to obtain few-layer graphene oxide.
[0016] In some embodiments, the mass ratio of graphite, sulfuric acid, sodium nitrate and phosphorus pentoxide is (1-2):(18-20):(1.5-2):(1.5-2);
[0017] The mass ratio of potassium permanganate to graphite is 5:1.
[0018] In some embodiments, the content of graphene oxide in the slurry is 7-10 mg / mL, and the concentration of sodium ascorbate is 0.2-0.3 mg / mL.
[0019] In some embodiments, the temperature of the hydrothermal treatment is 120-130°C.
[0020] In some embodiments, the freeze-drying in step S2 comprises:
[0021] The slurry after hydrothermal treatment is injected into the mold, and the mold is oriented and frozen from bottom to top by liquid nitrogen, and the freezing time is 10 to 15 minutes;
[0022] Then dry it at a temperature of -70 to -80°C and a vacuum degree of <15Pa for 24 to 48 hours.
[0023] In some embodiments, the temperature of the immersion treatment is 60-80° C. and the pressure is less than 100 Pa.
[0024] In some embodiments, the freeze-drying in step S4 comprises:
[0025] The vacuum impregnation product is frozen by liquid nitrogen for 10 to 15 minutes;
[0026] Then dry it at a temperature of -70 to -80°C and a vacuum degree of <15Pa for 24 to 48 hours.
[0027] The second aspect of the present application provides a molten salt phase change energy storage material prepared by the above preparation method.
[0028] The third aspect of the present application provides the use of the molten salt phase change energy storage material prepared by the above preparation method in solar thermal power station photothermal storage.
[0029] Compared with the prior art, the beneficial effects of this application are:
[0030] The present application utilizes graphene aerogel and solar salt as raw materials, and adopts a vacuum impregnation method to prepare a graphene-based molten salt phase change energy storage material, so that the molten salt can evenly penetrate the pores of the graphene aerogel. It combines the high porosity of graphene with the phase change energy storage characteristics of molten salt, significantly improving the thermal conductivity and phase change stability. The wetting angle between graphene and molten salt in the molten salt phase change energy storage material is very large, ensuring that the molten salt is not easy to leak, further improving the thermal conductivity, and is particularly suitable for energy storage of electronic equipment and photothermal conversion devices and systems with strict requirements. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] In order to more clearly illustrate the technical solutions of the embodiments of the present application, the following briefly introduces the drawings required for use in the description of the embodiments. Obviously, the drawings described below are only some embodiments recorded in the present application, and for ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.
[0032] Figure 1 This is a physical picture of the graphene aerogel prepared in Example 1;
[0033] Figure 2 This is a physical picture of the graphene aerogel after impregnation treatment in Example 1;
[0034] Figure 3 This is a scanning electron microscope image of the molten salt phase change energy storage material of Example 1;
[0035] Figure 4 This is a DSC (differential scanning calorimetry) test result diagram of the molten salt phase change energy storage material of Example 1;
[0036] Figure 5 This is a graph showing the thermal conductivity test results of the graphene aerogel, eutectic salt and molten salt phase change energy storage material prepared in Example 1. DETAILED DESCRIPTION
[0037] The technical solutions in the embodiments of the present application will be described clearly and completely below in conjunction with the drawings in the embodiments of the present application. Obviously, the described embodiments are part of the embodiments of the present application, rather than all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of this application.
[0038] In the following description of this embodiment, the terms "include", "comprising", "having" and "containing" are all open terms, meaning including but not limited to.
[0039] In the following description of this embodiment, the term "and / or" is used to describe the association relationship of associated objects, indicating that there may be three relationships. For example, A and / or B can represent: A exists alone, B exists alone, and A and B exist at the same time. A and B can be singular or plural. The character " / " generally indicates that the associated objects before and after are in an "or" relationship.
[0040] In the following description of this embodiment, the term "at least one" refers to one or more, and "plurality" refers to two or more. "At least one of the following" or similar expressions refers to any combination of these items, including any combination of single items or plural items. For example, "at least one of a, b or c", or "at least one of a, b and c", can all represent: a, b, c, ab (i.e., a and b), ac, bc, or abc, where a, b, c can be single or multiple, respectively.
[0041] The terms used in the embodiments of the present application are only for the purpose of describing specific embodiments, and are not intended to limit the present application. The singular forms "a", "an" and "the" used in the embodiments of the present application and the appended claims are also intended to include plural forms, unless the context clearly indicates other meanings.
[0042] Those skilled in the art should understand that in the following description of the embodiments of the present application, the order of serial numbers does not mean the order of execution, some or all of the steps can be executed in parallel or sequentially, and the execution order of each process should be determined by its function and internal logic, and should not constitute any limitation on the implementation process of the embodiments of the present application.
[0043] Those skilled in the art will appreciate that the numerical ranges in the embodiments of the present application are to be construed as specifically disclosing each intermediate value between the upper and lower limits of the scope. Each smaller range between the intermediate value in any stated value or stated range and any other stated value or intermediate value in the described range is also included in the present application. The upper and lower limits of these smaller ranges may be independently included or excluded in the scope.
[0044] Unless otherwise specified, the technical / scientific terms used herein have the same meanings as those generally understood by those skilled in the art to which this application belongs. Although this application only describes preferred methods and materials, any methods and materials similar or equivalent to those described herein may also be used in the implementation or testing of this application. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials related to the documents. In the event of a conflict with any incorporated document, the content of this specification shall prevail.
[0045] In a first aspect, the present application provides a method for preparing a molten salt phase change energy storage material, comprising:
[0046] S1, mixing NaNO3 and KNO3 in a mass ratio of 6:4, grinding and heating to 400°C to melt, cooling and grinding again to obtain a eutectic salt;
[0047] The grinding is carried out by a ball mill, the rotation speed of the ball mill is 300-500 rpm, the grinding time is 30-60 min, and the cooling rate during cooling is 5°C / min.
[0048] S2, dispersing the few-layer graphene oxide and sodium ascorbate in water, and mixing them evenly to obtain a slurry; the slurry is subjected to hydrothermal treatment and then freeze-dried to obtain a graphene aerogel;
[0049] The content of the few-layer graphene oxide in the slurry is 7-10 mg / mL, the concentration of sodium ascorbate is 0.2-0.3 mg / mL, the temperature of the hydrothermal treatment is 120-130° C., and the time of the hydrothermal treatment is preferably 12-24 hours. The hydrothermal treatment promotes the reduction and structural reorganization of the few-layer graphene oxide by sodium ascorbate.
[0050] In this step, the slurry after hydrothermal treatment is injected into the mold, and the mold is oriented and frozen from bottom to top by liquid nitrogen for 10 to 15 minutes; then it is dried for 24 to 48 hours at a temperature of -70 to -80°C and a vacuum degree of <15Pa. In this application, the mold is a cylinder with a diameter and height of 1 to 2 cm. After freeze drying, all water is removed to obtain a graphene aerogel with a porous structure.
[0051] S3, dissolving the eutectic salt in water to prepare a saturated solution, and immersing the graphene aerogel in the saturated solution under vacuum;
[0052] Specifically, the eutectic salt prepared in step S1 is dissolved in distilled water heated to near boiling, and stirring is continued until the eutectic salt is fully dissolved and salt particles begin to be unable to be further dissolved, thereby obtaining a saturated solution. The graphene aerogel is immersed in the saturated solution, so that the eutectic salt solution fully penetrates into the pore structure of the graphene aerogel.
[0053] To ensure uniform and complete penetration of the graphene aerogel and molten salt composite, a higher vacuum helps remove air and other gases from the pores of the material, allowing the molten salt to fill these spaces more effectively. The higher the vacuum, the lower the boiling point of water. To ensure the impregnation effect, the impregnation temperature is controlled between 60 and 80 ° C, the pressure is less than 100 Pa, and the impregnation time is 2 to 3 hours.
[0054] S4, freeze-drying the impregnated product to obtain a molten salt phase change energy storage material.
[0055] Specifically, the product after vacuum impregnation treatment is frozen by liquid nitrogen for 10 to 15 minutes, and then dried for 24 to 48 hours at a temperature of -70 to -80°C and a vacuum degree of <15 Pa. After freeze drying, the water in the graphene-molten salt composite material is removed to obtain a graphene-based molten salt phase change energy storage material.
[0056] In the present application, the few-layer graphene oxide is prepared by the following method:
[0057] Mix graphite and sulfuric acid evenly, add sodium nitrate and phosphorus pentoxide, stir at 80-100°C for 12-24h, separate and collect the solid phase, wash and shade-dry to obtain the precursor;
[0058] The precursor is dispersed in excess concentrated sulfuric acid, and potassium permanganate is slowly added thereto, stirred at -10 to 0°C, and then diluted with water, and then heated to 90°C, and hydrogen peroxide is added until the solution turns bright yellow to obtain a dispersion; the dispersion is diluted with water, centrifuged at a speed of 5000 to 7000 r / min to remove multilayer graphene oxide, and then centrifuged at a speed of 10000 to 12000 r / min to remove impurities, and the concentrated solution obtained by centrifugation is freeze-dried to obtain few-layer graphene oxide.
[0059] In the present application, the mass ratio of the graphite, sulfuric acid, sodium nitrate and phosphorus pentoxide is preferably (1-2):(18-20):(1.5-2):(1.5-2); the mass ratio of potassium permanganate to graphite is preferably 5:1.
[0060] This application uses graphene aerogel and solar salt as raw materials, and adopts a vacuum impregnation method to prepare a molten salt phase change energy storage material, so that the molten salt evenly penetrates the pores of the graphene aerogel; it combines the high porosity of graphene with the phase change energy storage characteristics of molten salt, significantly improving the thermal conductivity and phase change stability.
[0061] In the second aspect, the present application provides a molten salt phase change energy storage material prepared by the above preparation method. The molten salt phase change energy storage material combines the high porosity of graphene with the phase change energy storage characteristics of molten salt, significantly improving the thermal conductivity and phase change stability; wherein the wetting angle between graphene and molten salt is very large, ensuring that the molten salt is not easy to leak, further improving the thermal conductivity.
[0062] The molten salt phase change energy storage material prepared in the present application is particularly suitable for energy storage in electronic equipment and photothermal conversion devices and systems with strict requirements. It can be applied to photothermal storage in solar thermal power stations, as well as thermal energy storage and utilization in the steel, cement, and glass industries.
[0063] The present application is further described below by way of examples.
[0064] Example 1
[0065] This embodiment provides a method for preparing a molten salt phase change energy storage material, comprising:
[0066] S1, NaNO3 and KNO3 were mixed in a mass ratio of 6:4, and ground in a ball mill at a speed of 500 rpm for 60 min to obtain a mixed salt powder. The mixed salt powder was heated to 400°C to melt, then cooled at a cooling rate of 5°C / min, and ground again to obtain a eutectic salt;
[0067] S2, mix 2g of flake graphite with 10ml of sulfuric acid, stir at 80°C, then add 1.7g of sodium nitrate and 1.7g of phosphorus pentoxide in sequence, and continue stirring for 12 hours; filter the mixture twice and dry it in the shade at room temperature for 3 hours to obtain a precursor; add 80ml of sulfuric acid in a beaker, add the precursor, slowly add 10g of potassium permanganate to the beaker at -10°C, stir for 4.5 hours, then treat in a 35°C water bath for 4 hours, dilute it in 1000ml of water, and stir for 15 minutes; heat to 90°C and add hydrogen peroxide until the solution turns bright yellow to obtain a dispersion; centrifuge the dispersion at 11000r / min for 7min, then centrifuge at 6000r / min for 5min to remove impurities, and centrifuge again at 11000r / min for 15min to obtain a concentrate. Freeze-dry the concentrate for 48 hours to obtain few-layer graphene oxide;
[0068] 200 mg of few-layer graphene oxide was mixed with 5 mg of sodium ascorbate and 20 ml of water, and the mixture was shaken for 5 minutes. The mixture was hydrothermally treated at 130°C for 12 hours, and then the reaction mixture was poured into a cylindrical polyethylene mold with a diameter of 2 cm and a height of 2 cm. The mold was directionally frozen from bottom to top using liquid nitrogen for 15 minutes. After freezing, the mold was placed in a freeze dryer, the temperature was set to -70°C, the vacuum degree was <15 Pa, and it was dried for 48 hours to obtain a porous graphene aerogel.
[0069] S3, slowly add the eutectic salt to the distilled water heated to near boiling, and continue stirring until the salt is completely dissolved and salt particles begin to be unable to dissolve further, indicating that the solution has reached a supersaturated state. Place the graphene aerogel in the supersaturated solution, move it into a vacuum oven, heat it to 60°C under a pressure of less than 100Pa, and keep it warm and immerse it for 2 hours to ensure that the saturated solution fully penetrates into the pore structure of the graphene aerogel.
[0070] S4, freezing the impregnated product by liquid nitrogen for 10-15 minutes, and then drying it for 48 hours at a temperature of -80°C and a vacuum degree of <15Pa to obtain a molten salt phase change energy storage material.
[0071] Example 2
[0072] This embodiment provides a method for preparing a molten salt phase change energy storage material, comprising:
[0073] S1, NaNO3 and KNO3 were mixed in a mass ratio of 6:4, and ground in a ball mill at a speed of 500 rpm for 60 min to obtain a mixed salt powder. The mixed salt powder was heated to 400°C to melt, then cooled at a cooling rate of 5°C / min, and ground again to obtain a eutectic salt;
[0074] S2, mix 2g of flake graphite with 10ml of sulfuric acid, stir at 80°C, then add 1.7g of sodium nitrate and 1.7g of phosphorus pentoxide in sequence, and continue stirring for 12 hours; filter the mixture twice and dry it in the shade at room temperature for 3 hours to obtain a precursor; add 80ml of sulfuric acid in a beaker, add the precursor, slowly add 10g of potassium permanganate to the beaker at -10°C, stir for 4.5 hours, then treat in a 35°C water bath for 4 hours, dilute it in 1000ml of water, and stir for 15 minutes; heat to 90°C and add hydrogen peroxide until the solution turns bright yellow to obtain a dispersion; centrifuge the dispersion at 11000r / min for 7min, then centrifuge at 6000r / min for 5min to remove impurities, and centrifuge again at 11000r / min for 15min to obtain a concentrate. Freeze-dry the concentrate for 48 hours to obtain few-layer graphene oxide;
[0075] 150 mg of few-layer graphene oxide was mixed with 5 mg of sodium ascorbate and 20 ml of water, and the mixture was shaken for 5 minutes. The mixture was hydrothermally treated at 120°C for 12 hours, and then the reaction mixture was poured into a cylindrical polyethylene mold with a diameter of 2 cm and a height of 2 cm. The mold was directionally frozen from bottom to top using liquid nitrogen for 15 minutes. After freezing, the mold was placed in a freeze dryer, the temperature was set to -70°C, the vacuum degree was <15 Pa, and it was dried for 48 hours to obtain a porous graphene aerogel.
[0076] S3, slowly add the eutectic salt to the distilled water heated to near boiling, and continue stirring until the salt is completely dissolved and salt particles begin to be unable to dissolve further, indicating that the solution has reached a supersaturated state. Place the graphene aerogel in the supersaturated solution, move it into a vacuum oven, heat it to 70°C under a pressure of <100Pa, and keep it warm and immerse it for 2 hours to ensure that SS fully penetrates into the pore structure of the graphene aerogel.
[0077] S4, freezing the impregnated product by liquid nitrogen for 10-15 minutes, and then drying it for 48 hours at a temperature of -80°C and a vacuum degree of <15Pa to obtain a molten salt phase change energy storage material.
[0078] Example 3
[0079] This embodiment provides a method for preparing a molten salt phase change energy storage material, comprising:
[0080] S1, NaNO3 and KNO3 were mixed in a mass ratio of 6:4, and ground in a ball mill at a speed of 500 rpm for 60 min to obtain a mixed salt powder. The mixed salt powder was heated to 400°C to melt, then cooled at a cooling rate of 5°C / min, and ground again to obtain a eutectic salt;
[0081] S2, mix 2g of flake graphite with 10ml of sulfuric acid, stir at 80°C, then add 1.7g of sodium nitrate and 1.7g of phosphorus pentoxide in sequence, and continue stirring for 12 hours; filter the mixture twice and dry it in the shade at room temperature for 3 hours to obtain a precursor; add 80ml of sulfuric acid in a beaker, add the precursor, slowly add 10g of potassium permanganate to the beaker at -10°C, stir for 4.5 hours, then treat in a 35°C water bath for 4 hours, dilute it in 1000ml of water, and stir for 15 minutes; heat to 90°C and add hydrogen peroxide until the solution turns bright yellow to obtain a dispersion; centrifuge the dispersion at 11000r / min for 7min, then centrifuge at 6000r / min for 5min to remove impurities, and centrifuge again at 11000r / min for 15min to obtain a concentrate. Freeze-dry the concentrate for 48 hours to obtain few-layer graphene oxide;
[0082] 200 mg of few-layer graphene oxide was mixed with 5 mg of sodium ascorbate and 20 ml of water, and the mixture was shaken for 5 minutes. The mixture was hydrothermally treated at 130°C for 12 hours, and then the reaction mixture was poured into a cylindrical polyethylene mold with a diameter of 2 cm and a height of 2 cm. The mold was directionally frozen from bottom to top using liquid nitrogen for 15 minutes. After freezing, the mold was placed in a freeze dryer, the temperature was set to -70°C, the vacuum degree was <15 Pa, and it was dried for 48 hours to obtain a porous graphene aerogel.
[0083] S3, slowly add the eutectic salt to the distilled water heated to near boiling, and continue stirring until the salt is completely dissolved and salt particles begin to be unable to dissolve further, indicating that the solution has reached a supersaturated state. Place the graphene aerogel in the supersaturated solution, move it into a vacuum oven, heat it to 75°C under a pressure of <100Pa, and keep it warm and immerse it for 2 hours to ensure that SS fully penetrates into the pore structure of the graphene aerogel.
[0084] S4, freezing the impregnated product by liquid nitrogen for 10-15 minutes, and then drying it for 48 hours at a temperature of -80°C and a vacuum degree of <15Pa to obtain a molten salt phase change energy storage material.
[0085] The performance of the graphene aerogel and molten salt phase change energy storage material prepared in Example 1 was evaluated. Figure 1 This is a physical picture of the graphene aerogel prepared in Example 1. It has a regular shape and a complete structure, indicating that the preparation process is successful. The aerogel has good uniformity and has no obvious defects or uneven areas.
[0086] Figure 2 This is a physical picture of the graphene aerogel after impregnation in Example 1. Figure 2 It can be seen that the graphene aerogel has been fully infiltrated by the saturated salt solution, and the surface is uniformly wet, indicating that the solution has successfully penetrated into the internal structure of the aerogel, the impregnation effect is good, and the graphene aerogel has a good ability to be infiltrated by the saturated salt solution.
[0087] Figure 3 This is a scanning electron microscope image of the graphene aerogel after impregnation. Figure 3 It can be seen that the solar salt crystals are successfully loaded inside the graphene aerogel, with uniform distribution and high loading rate. The crystal morphology is regular and the crystallinity is good, indicating that during the impregnation process, the solar salt can effectively enter the pore structure of the aerogel and form high-quality crystals, further proving the excellent performance of graphene aerogel as a carrier in the adsorption and crystallization process.
[0088] Figure 4 This is a DSC (differential scanning calorimetry) test result diagram of the molten salt phase change energy storage material of Example 1. Figure 4 It can be seen that the composite material exhibits excellent phase change heat storage capacity and can effectively absorb and release heat within a specific temperature range, indicating that it has good thermal stability and energy storage performance.
[0089] The thermal conductivity of the graphene aerogel, eutectic salt and molten salt phase change energy storage material prepared in Example 1 was tested by a laser flash method, specifically including:
[0090] 1. Prepare samples: Cut and prepare samples in the shape of square slices.
[0091] 2. Install the sample: Fix the sample in the test equipment, making sure the sample surface is flat and in good contact with the equipment.
[0092] 3. Laser irradiation: Use short pulse laser to irradiate one side of the sample.
[0093] 4. Temperature measurement: Record the temperature response on the other side of the sample, usually using an infrared sensor.
[0094] 5. Data analysis: Calculate the thermal diffusion coefficient through the temperature response curve of the sample, and then calculate the thermal conductivity based on the density and specific heat capacity of the sample.
[0095] Test results such as Figure 5 As shown. Figure 5 It can be seen that the thermal conductivity of the molten salt phase change energy storage material is 0.712W / m·K, which is significantly higher than that of the single graphene aerogel (0.124W / m·K) and close to the thermal conductivity of solar salt (0.763W / m·K). This shows that the thermal conductivity of the composite material has been significantly improved, making it suitable for phase change energy storage applications.
[0096] Although the present application has been described in detail in general terms and in specific embodiments in this specification, it is obvious to those skilled in the art that some modifications or improvements may be made to the present application. Therefore, these modifications or improvements made without departing from the spirit of the present application are within the scope of protection claimed in the present application.
Claims
1. A method for preparing a molten salt phase change energy storage material, characterized in that: include: S1, mixing NaNO3 and KNO3 in a mass ratio of 6:4, grinding and heating to 400°C to melt, cooling and grinding again to obtain a eutectic salt; S2, dispersing the few-layer graphene oxide and sodium ascorbate in water, and mixing them evenly to obtain a slurry; the slurry is subjected to hydrothermal treatment and then freeze-dried to obtain a graphene aerogel; S3, dissolving the eutectic salt in water to prepare a saturated solution, and immersing the graphene aerogel in the saturated solution under vacuum; S4, freeze-drying the impregnated product to obtain a molten salt phase change energy storage material.
2. The preparation method according to claim 1, characterized in that: The few-layer graphene oxide is prepared by the following method: Mix graphite and sulfuric acid evenly, add sodium nitrate and phosphorus pentoxide, stir at 80-100°C for 12-24h, separate and collect the solid phase, wash and shade-dry to obtain the precursor; The precursor is dispersed in excess concentrated sulfuric acid, and potassium permanganate is slowly added thereto, stirred at -10 to 0°C, and then diluted with water, and then heated to 90°C, and hydrogen peroxide is added until the solution turns bright yellow to obtain a dispersion; The dispersion is diluted with water, centrifuged at a speed of 5000-7000 r / min to remove multilayer graphene oxide, and then centrifuged at a speed of 10000-12000 r / min to remove impurities, and the concentrated solution obtained by centrifugation is freeze-dried to obtain few-layer graphene oxide.
3. The preparation method according to claim 2, characterized in that: The mass ratio of graphite, sulfuric acid, sodium nitrate and phosphorus pentoxide is (1-2):(18-20):(1.5-2):(1.5-2); The mass ratio of potassium permanganate to graphite is 5:
1.
4. The preparation method according to claim 1, characterized in that: The content of graphene oxide in the slurry is 7-10 mg / mL, and the concentration of sodium ascorbate is 0.2-0.3 mg / mL.
5. The preparation method according to claim 1, characterized in that: In step S2, the temperature of the hydrothermal treatment is 120-130°C.
6. The preparation method according to claim 1, characterized in that: In step S2, the freeze-drying comprises: The slurry after hydrothermal treatment is injected into the mold, and the mold is oriented and frozen from bottom to top by liquid nitrogen, and the freezing time is 10 to 15 minutes; Then dry it at a temperature of -70 to -80°C and a vacuum degree of <15Pa for 24 to 48 hours.
7. The preparation method according to claim 1, characterized in that: The temperature of the immersion treatment is 60-80° C., and the pressure is less than 100 Pa.
8. The preparation method according to claim 1, characterized in that: The freeze drying in step S4 comprises: The vacuum impregnation product is frozen by liquid nitrogen for 10 to 15 minutes; Then dry it at a temperature of -70 to -80°C and a vacuum degree of <15Pa for 24 to 48 hours.
9. The molten salt phase change energy storage material prepared by the preparation method according to any one of claims 1 to 8.
10. Application of the molten salt phase change energy storage material prepared by the preparation method according to any one of claims 1 to 8 in photothermal storage in a solar thermal power station.
Citation Information
Patent Citations
Method for preparing graphene and inorganic salt high-temperature phase change composite material
CN102344779A
Molten salt material with high energy storage density and preparation method thereof
CN115746798A
Method for preparing graphene
US20140037531A1
Heat transfer fluid comprising a molten salt and graphene
WO2016074092A1
Cited By
Graphene / lithium salt eutectic composite phase change material as well as preparation method and application thereof
CN120442223A
Composite phase change material capable of efficiently storing and exchanging heat and preparation method of composite phase change material
CN120464369A
High-efficiency heat storage and exchange composite phase change material and preparation method thereof
CN120464369B